ANALISIS KINERJA LALU LINTAS RUAS JALAN BIRUGO PUHUN AKIBAT OPERASIONAL PUSKESMAS TERATAI BIRUGO DATUAK BANDARO KOTA BUKITTINGGI - Rahmad Septian; Surya Eka Priana; Zulhedi Zulhedi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Birugo Puhun Road is a secondary collector road in Bukittinggi City with a width of approximately 6 meters and an effective lane width of about 4 meters. It experiences relatively heavy traffic volumes, especially during peak hours due to activities related to boarding houses, small shops, residential areas, and other surrounding land uses. The addition of a public facility, namely the Teratai Birugo Datuak Bandaro Community Health Centers, has the potential to increase traffic volume and side friction. Therefore, this study aims to analyze the traffic performance on this road segment as a result of the health center’s operation. The data used include both primary and secondary data, such as population, existing road conditions, traffic volume, and side friction. The analysis was conducted based on the Indonesian Road Capacity Guidelines (PKJI) 2023. The results indicate that the highest traffic volume is 309 passenger car units per hour (pcu/h), the highest side friction class is 103 events per hour, the road capacity is 1,220 pcu/h, and the degree of saturation is 0.25, with the level of service classified as category B. It can be concluded that the operation of the Teratai Birugo Datuak Bandaro Community Health Centers has not had a significant effect on the traffic performance of Birugo Puhun Road. However, field conditions, particularly during peak hours, show that traffic flow tends to approach unstable conditions due to the narrow road width and increasing side friction.Keywords: Traffic Volume, Side Friction Class, Capacity, Degree of Saturation